2019
DOI: 10.3390/agronomy9030135
|View full text |Cite
|
Sign up to set email alerts
|

Variability among Young Table Grape Cultivars in Response to Water Deficit and Water Use Efficiency

Abstract: Climate change will lead to higher frequencies and durations of water limitations during the growing season, which may affect table grape yield. The aim of this experiment was to determine the variability among 3-year old table grape cultivars under the influence of prolonged water deficit during fruit development on gas exchange, growth, and water use efficiency. Six own rooted, potted table grape cultivars (cv. ‘Muscat Bleu’, ‘Fanny’, ‘Nero’, ‘Palatina’, ‘Crimson Seedless’ and ‘Thompson Seedless’) were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
0
4
0
2
Order By: Relevance
“…Contrary to these findings, long-term results indicated that grain number per spike was the main factor that affected grain yield in lower mean temperature growing season while 1000-grain weight was the main factor that influenced grain yield in growing seasons with higher mean temperature, respectively. The reason might be that water was the first limiting factor determining the grain yield formation and could affect the contributions of yield components to yield [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these findings, long-term results indicated that grain number per spike was the main factor that affected grain yield in lower mean temperature growing season while 1000-grain weight was the main factor that influenced grain yield in growing seasons with higher mean temperature, respectively. The reason might be that water was the first limiting factor determining the grain yield formation and could affect the contributions of yield components to yield [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies apply crop modeling to better understand the impact of climate change on grapevines [4,17,18]. Furthermore, this special issue contains articles devoted to improving water use efficiency [19] and the effect of a natural anti-transpirant on grapevines [20]. Additionally, another study makes use of reflectance indices to assess vine water status [21].…”
Section: The Special Issuementioning
confidence: 99%
“…Increasing temperatures have resulted in higher reference evapotranspiration and more frequent years with low rainfall, and will continue to induce more intense and frequent drought conditions for vineyards around the world (Leeuwen et al, 2019). Water is also one of the most limiting factors for global grape production (Costa et al, 2007, Carolin et al, 2019. It is expected that climate change will generally have a negative impact on grape production.…”
Section: Introductionmentioning
confidence: 99%